Assessment of the Braking System Damage in the Public Transport Vehicles of a Selected Transport Company - Rybicka, Iwona; Droździel, Paweł; Komsta, Henryk (Periodica Polytechnica Transportation Engineering, 2023)
This paper analyzes damage to safety systems over a five-year period for a group of vehicles. In the first step of analysis, descriptive statistics characterizing the analyzed variables were calculated and analyses related to the assessment of damage to the braking system. The analyses were carried out in order to examine the relationship between the mileage of vehicles and the number of defects quarterly and monthly and the fit of the obtained empirical results of the analysed variables to a normal or other theoretical distribution was checked. In order to check whether the observed differences in the mean values of the number of failures of the safety systems are statistically significant, a non-parametric analysis of variance was performed. The Kolmogorov-Smirnov test was applied, the distribution of the monthly sum of the braking system faults, distribution of the sum of the braking system faults from individual quarters, distribution of the monthly kilometrage of all vehicles and distribution of the quarterly kilometrage of all vehicles were presented. After describing previous correlation analyses, a linear regression analysis was conducted in which a model was built to predict the number of braking system faults based on monthly vehicle mileage and month of measurement. The last part of the analysis was to verify whether the number of the braking systems faults depends on the season of the year and it was checked whether the season makes any difference to the vehicle's quarterly kilometrage. One-way analysis of variance (ANOVA) was carried out to this end.